Performance mecânica na produção dos Livros que não tenho e outros livros de artista impressos em tipografia no Brasil - Flávio Vignoli Cordeiro (2020)
This research-creation aims to investigate the creative process and production strategies of artist’s books printed in typography in Brazil and produce an authorial artist’s book. The structure of the writing and the graphic design of this research-creation allows the contents to be read separately or in the sequence proposed for the five chapters, in addition to the introduction and conclusion: “Manual prático para a tipografia”, “Álbum de referências”, “Caderno de anotações”, “Tipografia do Zé e a Coleção Livros que Não Tenho” and “Performance mecânica em tipografia”. The contents of the chapters present the basic knowledge for typography and its design, language and methodology; the needs for learning and practical knowledge for the creative process and for typography experimentation strategies; the historical references of figurative, graphic and plastic typography with notes on its strategies of composition and printing, typographic syntax and materiality; visual analysis by the “Gramática visual para a tipografia” of the four books of selected artists; the editorial history of Tipografia do Zé and the production strategies of the Coleção Livros que Não Tenho and the artist’s book A ave Wlademir Dias-Pino; the concept of mechanical performance for typography; and a methodology for contemporary typography. In this research-creation methodologies of material bibliography and oral history were used.